Influence of Catheter–Incision Congruency in Epidural Analgesia on Postcesarean Pain Management: A Single-Blinded Randomized Controlled Trial - Ying-Hsi Chen (MDPI AG, 2021)
Patient-controlled epidural analgesia (PCEA) or epidural morphine may alleviate postcesarean pain; however, conventional lumbar epidural insertion is catheter–incision incongruent for cesarean delivery. Methods: In total, 189 women who underwent cesarean delivery were randomly divided into four groups (low thoracic PCEA, lumbar PCEA, low thoracic morphine, and lumbar morphine groups) for postcesarean pain management. Pain intensities, including static pain, dynamic pain, and uterine cramp, were measured using a 100 mm visual analog scale (VAS). The proportion of participants who experienced dynamic wound pain with a VAS score of >33 mm was evaluated as the primary outcome. Adverse effects, including lower extremity blockade, pruritus, postoperative nausea and vomiting, sedation, and time of first passage of flatulence, were evaluated. Results: The low thoracic PCEA group had the lowest proportion of participants reporting dynamic pain at 6 h after spinal anesthesia (low thoracic PCEA, 28.8%; lumbar PCEA, 69.4%; low thoracic morphine, 67.3%; lumbar morphine group, 73.9%; p < 0.001). The aforementioned group also reported the most favorable VAS scores for static, dynamic, and uterine cramp pain during the first 24 h after surgery. Adverse effect profiles were similar among the four groups, but a higher proportion of participants in the lumbar PCEA group (approximately 20% more than in the other three groups) reported prolonged postoperative lower extremity motor blockade (p = 0.005). In addition, the first passage of flatulence after surgery reported by the low thoracic PCEA group was approximately 8 h earlier than that of the two morphine groups (p < 0.001). Conclusions: Epidural congruency is essential to PCEA for postcesarean pain. Low thoracic PCEA achieves favorable analgesic effects and may promote postoperative gastrointestinal recovery without additional adverse effects.